Facilitating circular permutation using Restriction Free (RF) cloning. Issue 3 (29th November 2017) - Bandyopadhyay, Boudhayan; Peleg, Yoav
Abstract: Circular permutation is a powerful tool to test the role of topology in protein folding and function. Previous methods for generating circular permutants were based on rearranging gene elements using restriction enzymes-based cloning. Here, we present a Restriction Free (RF) approach to achieve circular permutation which is faster and more cost-effective.